Room‐Temperature, Metal‐Free, and One‐Pot Preparation of 2H‐Indazoles through a Mills Reaction and Cyclization Sequence. Issue 42 (1st July 2019) - Kondo, Masaru; Takizawa, Shinobu; Jiang, Yuzhao; Sasai, Hiroaki
Abstract: The Mills reaction and cyclization of readily available 2‐aminobenzyl alcohols and nitrosobenzenes using thionyl bromide provided 2 H ‐indazoles in up to 88 % yields. In the metal‐free process, acetic acid played a crucial role for the both Mills reaction and cyclization. A brominated 2 H ‐indazole could also be obtained through the one‐pot sequence. Abstract : Heterocycles : The Mills reaction and cyclization of readily available 2‐aminobenzyl alcohols and nitrosobenzenes using thionyl bromide provided 2 H ‐indazoles in up to 88 % yields (see scheme). In the metal‐free process, acetic acid played a crucial role for the both Mills reaction and cyclization. A brominated 2 H ‐indazole could also be obtained through the one‐pot sequence.